Factors influencing hospital foodservice staff's capacity to deliver a nutrition intervention. Issue 2 (April 2017) - Collins, Jorja; Huggins, Catherine E.; Porter, Judi; Palermo, Claire
Abstract : Aim: Implementation of an intervention can result in a discrepancy between what was planned and what is delivered, affecting outcomes for recipients. The aim was to explore, from the perspective of hospital foodservice staff, their experiences delivering a nutrition intervention and the barriers and enablers to its implementation. Methods: A process evaluation of a pilot study was undertaken using qualitative description. A purposive sample (n = 15) of hospital foodservice supervisors and foodservice assistants responsible for delivering a higher energy menu to hospital patients participated in focus groups and semistructured interviews. Theoretical frameworks of behaviour underpinned the method. Content analysis elicited factors (sub‐themes) influencing foodservice staff's capability, opportunity and motivation to provide the nutrition intervention. Thematic analysis (by two independent researchers) further explored factors (themes) related to the process of the intervention's implementation. Results: Five key themes (and 15 sub‐themes) explained factors effecting implementation of the nutrition intervention. Aspects of the foodservice environment and patients' resistance were barriers to implementation and perceived sustainability. Teamwork, problem solving, leadership and job satisfaction were enablers. There was an opportunity to optimise training and feedback. Characteristics of foodservice staff, including their: knowledge, beliefs and perceptions of diet, health and their job role, had the potential to influence their behaviours and decision making. Conclusions: A number of interacting factors influenced foodservice staff's delivery of a higher energy menu as planned. Addressing the challenges of time, foodservice structure, patients' resistance, gaps in knowledge and misconceptions among foodservice staff may enhance similar nutrition interventions in the future.